Phytoplankton distribution in unusually low sea ice cover over the Pacific Arctic - P. Coupel; H. Y. Jin; M. Joo; R. Horner; H. A. Bouvet; M.-A. Sicre; J.-C. Gascard; J. F. Chen; V. Garçon; D. Ruiz-Pino (Biogeosciences, 2012)
A large part of the Pacific Arctic basin experiences ice-free conditions in summer as a result of sea ice cover steadily decreasing over the last decades. To evaluate the impact of sea ice retreat on the marine ecosystem, phytoplankton in situ observations were acquired over the Chukchi shelf and the Canadian basin in 2008, a year of high melting. Pigment analyses and taxonomy enumerations were used to characterise the distribution of main phytoplanktonic groups. Marked spatial variability of the phytoplankton distribution was observed in summer 2008. Comparison of eight phytoplankton functional groups and 3 size-classes (pico-, nano- and micro-phytoplankton) also showed significant differences in abundance, biomass and distribution between summer of low ice cover (2008) and heavy ice summer (1994). Environmental parameters such as freshening, stratification, light and nutrient availability are discussed as possible causes to explain the observed differences in phytoplankton community structure between 1994 and 2008.